PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2014-2019 - Alvenina, Felicia Quinta Yulia (Media Akuntansi dan Perpajakan Indonesia, 2021)
Tax is one of the largest state revenues so that the government tries to maximize tax revenue but it is different from companies that want to minimize taxes. In minimizing the tax, the company implements tax avoidance. The company avoids tax due to the lack of internal supervision of the company, therefore the need for a system that directs and regulates the relationships of interested company side in making policies within the company. The system is good corporate governance. The purpose of this study was to determine the effect of good corporate governance on tax avoidance. Good corporate governance in this study is proxied by executive compensation, institutional ownership, managerial ownership, independent board of commissioners, audit committee, and audit quality. Tax avoidance is measured using the Cash Effective Tax Rate (CETR). The research sample was 47 mining sector companies listed on the IDX in 2014–2019, and obtained 213 research data. The results in this study say that executive compensation has a negative effect on tax avoidance, institutional ownership and managerial ownership have a positive effect on tax avoidance and the independent board of commissioners, audit committee, audit quality has no effect on tax avoidance.